Strategi Pembelajaran Menulis Puisi Reflektif untuk Siswa SMA Kelas X - Etsa Purbarani; Abdus Syukur Ghazali; Nita Widiati (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Writing poetry learning in school tends to be mechanistic and less direct students in creative process that cause difficulty and decrease students’ motivation on writing poetry. Therefore, the researcher develops poetry writing learning strategy, that is learning strategy of writing reflective poetry which is packaged in a guidebook designed for teachers. Based on those explanations, this development aims to (1) developing products in the form of learning strategies to write reflective poems, (2) develop a guide of the implementation of a reflective poetry writing strategy that designed for teachers, and (3) reported the product feasibility test of reflective poetry writing strategy.Abstrak: Selama ini, pembelajaran menulis puisi di sekolah cenderung bersifat mekanistik dan kurang mengarahkan siswa untuk berproses kreatif. Hal tersebut menjadikan siswa mengalami kesulitan dan penurunan motivasi dalam menulis puisi. Oleh karena itu, dikembangkan strategi pembelajaran menulis puisi, yaitu strategi pembelajaran menulis puisi reflektif yang dikemas dalam bentuk buku panduan dan ditujukan untuk guru. Berdasarkan paparan tersebut, penelitian pengembangan ini bertujuan untuk (1) mengembangkan produk berupa strategi pembelajaran menulis puisi reflektif, (2) mengembangkan panduan penerapan strategi pembelajaran menulis puisi reflektif yang penggunaannya ditujukan untuk guru, dan (3) melaporkan uji kelayakan produk strategi pembelajaran menulis puisi reflektif.